Free to Seek and to Love the Creator: Fundamental Principle of Christian Education - Luis Mariano Bartoli (Nicolaus Copernicus University in Toruń, 2021)
The education of the person supposes the formation of his freedom. Maritain says that 'man is born free but is called to conquer his freedom'. To educate is to help the person to be more perfectly free. However, in our times, freedom is often misunderstood and is reduced to simple choice. For this reason, in this article we will reflect, following the teachings of Karol Wojtyla, John Paul II and the Gaudium et Spes Constitution, on the most profound sense of freedom that should guide true educational action.